Patterns of treatment with antiplatelet therapy after an acute coronary syndrome: Data from a large database in a community setting. (29th August 2020) - Cimminiello, Claudio; Dondi, Letizia; Pedrini, Antonella; Ronconi, Giulia; Calabria, Silvia; Piccinni, Carlo; Polo Friz, Hernan; Martini, Nello; Maggioni, Aldo P
Abstract: Aims: Current guidelines strongly recommend antiplatelet therapy with aspirin plus a P2Y12 receptor inhibitor (dual therapy) for patients with acute coronary syndrome (ACS). To better understand how antiplatelet treatment is prescribed in clinical practice, the aim of this study was to provide a more detailed description of real-world patients with and without antiplatelet treatment after an ACS, their outcomes at one-year follow-up and the related integrated cost. Methods: The ReS database, including more than 12 million inhabitants, was evaluated. During the accrual period ACS patients discharged alive were identified on the basis of ICD-IX-CM code. Antiplatelet drug prescriptions and healthcare costs were analysed over one-year follow-up. Results: In 2014, of the 25, 129 patients discharged alive after an ACS, 5796 (23%) did not receive any antiplatelet therapy during the first month after hospital discharge. Among them, 3846 (66%) subjects were prescribed an antiplatelet drug subsequently, while 7.7% did not receive any antiplatelet treatment during the whole following year. Dual therapy in the subgroup of patients undergoing a revascularization procedure ( n  = 8436) was prescribed to 79.2% of cases and to 46.1% ( n  = 4009) of medically managed patients. The patients not treated with an antiplatelet treatment in the first month showed the highest one-year healthcare costs, mostly due to hospital re-admissions. Conclusions: This analysis of a large patient community shows that a considerable proportion of patients remained untreated with antiplatelet treatment after an ACS event. A clearer characterization of these subjects can help to improve the adherence to the current guidelines and recommendations.